2011
DOI: 10.1093/intimm/dxr088
|View full text |Cite
|
Sign up to set email alerts
|

The CD40-CD40L axis and IFN-  play critical roles in Langhans giant cell formation

Abstract: The presence of Langhans giant cells (LGCs) is one of the signatures of systemic granulomatous disorders such as tuberculosis and sarcoidosis. However, the pathophysiological mechanism leading to LGC formation, especially the contribution of the T cells abundantly found in granulomas, has not been fully elucidated. To examine the role of T cells in LGC formation, a new in vitro method for the induction of LGCs was developed by co-culturing human monocytes with autologous T cells in the presence of concanavalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 43 publications
1
42
0
Order By: Relevance
“…Our team recently reported that the fusion process could be triggered in a TLR2-dependent cell activation by mycobacterial lipomannan (but not lipoarabinomannan), and that this process was dependent on a ß1 integrin/ADAM9 pathway [47]. Another very recent study showed that the coculture of macrophages with activated T cells can lead to MGC formation through CD40/CD40L interaction and IFN- γ secretion [48]. MGCs are found only in the granulomas induced by Mtb.…”
Section: The Principal Cell Populations Involved In the Granulomatmentioning
confidence: 99%
“…Our team recently reported that the fusion process could be triggered in a TLR2-dependent cell activation by mycobacterial lipomannan (but not lipoarabinomannan), and that this process was dependent on a ß1 integrin/ADAM9 pathway [47]. Another very recent study showed that the coculture of macrophages with activated T cells can lead to MGC formation through CD40/CD40L interaction and IFN- γ secretion [48]. MGCs are found only in the granulomas induced by Mtb.…”
Section: The Principal Cell Populations Involved In the Granulomatmentioning
confidence: 99%
“…This observation strongly supports the predominant role of IL-23 in mediating Th17 cell response. Notably, the GC-mediated DC-T cell interaction in promoting the Th1 and Th17 responses in 9V/null mice may also relate to its efficiency in inducing the CD40L expression, as CD40-CD40L crosstalk is important to the Th1 and Th17 responses [30, 47–50]. These results support GC as promoting the engagement of CD40 through T cell CD40L; This is a critical step for T cells activation and up-regulation of Th1 and Th17 immune responses [30, 43, 51, 52].…”
Section: Discussionmentioning
confidence: 99%
“…The macrophage maturation factors alone do not induce fusion [85,86]. Stimulation with IL-4 or IL-13 in vitro results predominantly in foreign-body giant cell formation, while stimulation with IFNγ results predominantly in Langhans giant cell formation [87]. Other factors suggested to stimulate MGC formation include α-tocopherol (a form of vitamin E) [88], calcitriol (1,25-dihydroxyvitamin D3) [89], phorbol 12-myristate 13-acetate [90], and T-cell mitogenic plant lectins concanavalin A and phytohemagglutinin [91].…”
Section: Environment/generationmentioning
confidence: 99%